Empowerment of Youth in Optimizing Adolescent Reproductive Health in Sukamandi Village, Sagalaherang District, Subang Regenc - Ruciah Ruciah; Lingga Khoirotul Aniiq (Journal of World Science, 2025)
Adolescent reproductive health is an important aspect in shaping a healthy and productive generation, yet many young people face significant challenges due to limited knowledge and access to appropriate health information and services. Research problems identified include high rates of adolescent reproductive health issues such as unwanted pregnancies, sexually transmitted infections, and anemia, particularly in rural areas where access to information and healthcare services remains limited. This study aims to evaluate the effectiveness of adolescent empowerment programs in optimizing reproductive health knowledge, attitudes, and service utilization among adolescents in Sukamandi Village, Sagalaherang District, Subang Regency. The research method used was community-based participatory research (CBPR) involving 50 adolescents aged 13-19 years selected through purposive sampling. Interventions included comprehensive reproductive health training sessions, formation of youth health cadres, peer education programs, and social media-based educational campaigns implemented over a four-month period from February to May 2025. Results showed significant improvements, with reproductive health knowledge increasing by 45% (from baseline mean score of 65.2 to post-intervention score of 94.5), utilization of adolescent health services at the Health Center increasing by 30%, positive attitudes towards healthy living behaviors improving by 40%, and successful establishment of 8 peer education sessions conducted by trained youth cadres. The implications of this research demonstrate that community-based youth empowerment approaches can serve as effective strategies for improving adolescent reproductive health outcomes in rural settings, providing a sustainable model for scaling up similar interventions in comparable communities across Indonesia.